“I’M A SUPERHERO”: INCREASING STUDENTS’ PSYCHOLOGICAL CAPITAL THROUGH STORYTELLING - Unika Prihatsanti; Ika Zenita Ratnaningsih; Anggun Resdasari Prasetyo (Jurnal Cakrawala Pendidikan, 2020)
Psychological capital as a positive psychological characteristic that reflected through several components such self-efficacy, hope, optimism, and resilience is important to adjust the changes that experienced by freshmen in a college. Storytelling is a form of communication that allows the listener to fully immerse in the content of the story and experience the emotions felt by the characters. This study aims to determine the effect of storytelling activities use “I’m a Superhero” module to increase students’ psychological capital. Quasi-experimental methods were used in the study that involving 127 first-year college students. The subjects of this study divided into two groups, 56 for the experimental group and 71 for the control group. The interventions were done for 22 days divided into six sessions and described in "I'm a Superhero" module. The analysis results using an independent sample t-test showed that there was a difference between experiment and control groups (t(125) = 5.176; p .01). It shows that the storytelling activity is the potential to be an alternative media to increasing students' psychological capital so that the freshmen more independent and quickly adjust to change.